KARTU KREDIT SYARIAH DAN PERILAKU KONSUMTIF MASYARAKAT - Dewi Sukma Kristianti (AHKAM : Jurnal Ilmu Syariah, 2014)
Islamic Credit Cards and Consumptive Behaviour of Society. The credit card as one means of payment utilising cards, is a payment system that is growing rapidly, brought about by the security and risk of carrying cash in large amounts, efficiency, speed and ease of transaction that is offered. Islamic banks are glancing consumer funding products as one of the products services to be offered. There is a very important limitation that must be realized for Islamic banks, namely the provisions of the shari’a principles regarding the provision of credit card and influence on consumer  behaviour  society,  particularly  the  Muslim  community.  It  is  not  impossible  for  the  existence  of  Islamic credit cards that are presented for the ease of transacting to become a card for the ease of indebtedness and cause a consumptive/wasteful attitude that is definitely forbidden in Islamic economic concept.DOI: 10.15408/ajis.v14i2.1287